MENHECU'S-SELEFI'S-SALIH FI TEFSIRI SIFATI'LLAHI'L-HABERIYYE - SALEH, MAHMOUD AL (Fırat Üniveristesi, 2018)
Allah'ın kelâmını en güzel şekilde anlayan ve onu en doğru şekilde tefsir edenler selef-i sâlih dediğimiz sahâbe, tâbiîn ve tebe-i tabiîndir. Hayır, bereket, güzel anlayış, doğru söz ve olgun ahlak sahibi olduklarına şehâdet edilmiş ilk üç nesil onlardır. Selef-i salihîn, Allah'ın kelâmına iman etmiş ve onu hakkıyla anlamışlardır. Onlar, Allah'ı ve sıfatlarını yine Allah'ın Kuran'da zikrettiği ve Hz. Peygamber'den (s.a.v) sahih bir şekilde rivayet edildiği gibi bilmişler ve bunlara gerek icmal gerekse de tafsil ile iman getirmişlerdir. Allah'ın kendi hakkında nefyettiği, kendine yakışmayacak her türlü noksanlığı ve yaratılmışlara benzemediği onlar da, Allah hakkında nefyetmişlerdir. Yaratılmışların cüz ve azalarına delalet eden "el, göz, ayak, yan, gelmek, getirmek v.s." sıfatlar da lafzın zahiri itibariyle Allah'ın sıfatlarındandır ve bunlar, Kur'an ve Sünnet'in sâdık haberiyle sâbit oldukları için haberî sıfatlar diye isimlendirilmişlerdir. Fakat akıl bunları olduğu gibi kabul edemez. Çünkü bu, Kur'ânî lafızların zâhiri, başka ayetlerle sabit olan "Allah'ın mahlûkata bezememesi ve mutlak kemal sıfatlarıyla muttasıf olması" kaidelerine aykırıdır. İşte selef, Allah'ın kelâmını ve sıfatlarını tefsir ederken, hepsine iman ettiklerini söyleyip ne sıfatlarını nefyetmiş ne de O'nu yaratılmışlara benzetmişlerdir. Bazıları, direkt Allah'ın muradına havale etmiş, bazıları da Arap dili kaidelerine uygun şekilde tevil yoluna gitmişlerdir. Fakat hepsi de bu sıfatlarla ilgili zihne ilk gelen "mahlûkatın cüz ve hareketlerine benzeme" manasını nefyetmişlerdir. Çünkü Allah, muhkem ayetlerde açıkça, hiçbir yaratılmışa benzemediğini, vehim ve zanlar ile ihata edilemeyeceğini bildirmiştir.

The best people who understood the speech of Allah and explained it well are the righteous ancestor of the Prophet's companions and the followers and the followers of the followers. They are the first three generations that are known for charity, blessing, good understanding, rightness of saying, good faith, and good morals. They believed in the speech of Allah and and fully understood it and knew Allah and his qualities mentioned by Allah and that the Prophet peace be upon him considered correct. They believed in it altogether and denied that Allah denied for himself and denied all that didn't suit him like deficiency and similarity to the creatures. Some attributes of Allah are those that their appearance similar to the pronunciation of parts of the creatures like hand, eye, leg, side and coming and others, and these were called news attributes because they came true from the Koran and Sunna, and the mind didn't indicate them. The appearance of these Koranic words contradict with what is fixed in other verses of the denial of the similarity of Allah to creatures and his absolute perfection. The righteous ancestor mentioned their speech in the interpretation of the speech of Allah and His attributes, so they believed in them and did not disrupt and did not resemble. Some of them authorized the knowledge intended to Allah, and some of them interpreted according to and as required by the rules of the Arabic language , and all of them agreed that the apparent manifestation of those words and what the appearance of similarity of Allah to His creations in the parts and the pieces and movement they denied all of that about Allah because of the explicit statement of Allah in His arbitrator Download that Allah is immune from the similarity of creatures all and He Almighty is not surrounded by illusions and is not realized by suspicion.
Method of the righteous advances in the interpretation of the attributes of god news in The Quran
Keywords: Din